Theoretical-philosophical conceptions in the training of graduate students in nursing (Research, Society and Development, 2020)
The study aims to reflect on the experience lived by graduate students in nursing in a discipline of theoretical-philosophical conceptions in the process of caring in nursing and health. This is a descriptive reflection study, developed from the experiences of master students in a discipline of a postgraduate program in nursing, in the southern region of Brazil, which took place from March to July 2019. Those in charge run three centers: Philosophy in the Health and Nursing Care Process; Currents of Thought in the Health and Nursing Area; Philosophy in the Training of Nursing Graduate Students. The reflection enabled the identification of the competence importance of the theoretical-philosophical conceptions of the health and nursing care process and its contribution to professional training. It is concluded that the theoretical-philosophical conceptions are based as an important element in the training of graduate students in nursing, valuing a philosophical reflection as a knowledge construction strategy.